2017
DOI: 10.1021/acs.langmuir.7b02044
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption in the Ionic Liquids Immobilized on Solid Surface by Molecular Dynamics Simulation

Abstract: Based on our previous experimental research, we studied the absorption of CO in the ionic liquid, 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([hmim][TfN]), immobilized on TiO [rutile (110) ] with different thickness by molecular dynamics simulation. The effects of the properties (hydrophobicity and hydrophilicity) of solid interfaces were also studied with IL immobilized on graphite and TiO, respectively. We studied the influence of the thickness of IL immobilized on TiO on the absorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In addition, the phosphines bonded to two and three guanidine groups have been examined. There are numerous studies related with CO2 including in catalysis [25], processing polymers [26], engineering [27], absorption processes [28,29], crop development [30], fuels [31], lasers [32], and combustion research [33]. Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the phosphines bonded to two and three guanidine groups have been examined. There are numerous studies related with CO2 including in catalysis [25], processing polymers [26], engineering [27], absorption processes [28,29], crop development [30], fuels [31], lasers [32], and combustion research [33]. Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies related with CO2 including in catalysis [25], processing polymers [26], engineering [27], absorption processes [28,29], crop development [30], fuels [31], lasers [32], and combustion research [33]. Also, the CO2 molecule has been the subject of investigation from the theoretical point of view [29,34,35]. Our previous studies concerning A•••B complexes with B being CO2 are reported in references [36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we examined the diffusion coefficients (D) of cation and anion, respectively, with respect to water contents using the Einstein relation. 38 As summarized in Fig. 5, it is found that the values of D of both anion and cation in hydrated ILs quickly increase with the increase of water content.…”
Section: Diffusions Of Ilsmentioning
confidence: 86%
“…It is also reported that the thin IL lm on the substrate can enhance the connement effect, which accelerates its diffusion and the adsorption of CO 2 . 14,15 Despite these previous studies, the molecular mechanism of how IL molecules interact with the CO 2 gas in the conned space is still poorly documented, which becomes the main hindrance for further experimental research.…”
Section: Introductionmentioning
confidence: 99%